Optimalisasi Minat Pengunjung dengan Pendampingan Strategi Digital Taman Sokosewu Sukorejo Ponorogo - Choirul Wahid, Imam Mustofa; Setyawan, Agus (Institut Agama Islam Sunan Giri Ponorogo, 2024)
We should know in detail the characteristics, strengths and weaknesses of the village, so that village development can be in accordance with the potential of the village to be sold, in this case, lokal residents can participate in village development, so that they can be used as subjects in the development of their village. One of the efforts made is by way of community empowerment. The method of implementation is to coordinate with the head of Sukorejo village to obtain an overview of the profile and geographical conditions and demographics of the village, then conduct a survey of each hamlet to determine the state and digital capabilities of the community members, the next stage is to create an email account for the community and the technical stage of socialization is to carry out digital literacy. Through digital literacy activities, it can open insight and knowledge for the residents of Sukorejo village, Sukorejo district to build digital literacy and use digital technology approopriately. The public can take advantage of digital means for the promotion and marketing of brands or propducts through digital media and digital media can reach a wider and cost- efficient market.